500PClinico-molecular characteristics of Chinese primary non-small cell lung cancer patients with compound EGFR mutations. (24th November 2019) - Duan, J; Bai, H; Wang, X; Wan, R; Cheng, H; Wang, H; Lou, F; Cao, S; Wang, J
Abstract: Background: With the advances of next-generation sequencing (NGS), compound EGFR mutations were more frequently observed. Prior studies reported that patients with compound EGFR mutations showed poor clinical outcome. However, molecular and clinical features of NSCLC patients harboring such mutations were poorly investigated. Methods: A total of 1091 primary NSCLC patients were enrolled. Variants of EGFR and other driver genes were analyzed by NGS. EGFR exon 19 deletion (19 del) and L858R mutations were defined as common sensitizing mutations; EGFR G719S/C/A mutations were defined as uncommon sensitizing mutations; other mutations were defined as rare mutations. Patients were divided as follows: common sensitizing and rare mutations (group A); uncommon sensitizing and rare mutations (group B); double rare mutations (group C). Results: Overall, EGFR mutations were detected in 418 patients (38.3%), and 76 cases (7.0%) carried compound EGFR mutations. Frequencies of group A, B and C were 76.3%, 18.4% and 5.3%, respectively, indicating compound mutations mainly consist of sensitizing and atypical mutations. Compound mutations were more frequently observed in young patients (p = 0.017), and distributions of the three groups were different between early and adavanced stages (p = 0.032). According to types of common sensitizing mutations, rate of compound mutations harboring EGFR L858R alteration was strikingly higher than that carrying EGFR 19 del alteration (p = 0.039). Further analysis demonstrated that frequency of EGFR T790M mutation among the three groups showed significant difference (p = 0.031). Genomic data revealed TP53 mutations markedly coexisted with compound mutations compared with single mutation (p = 0.03). Moreover, relative EGFR mutant allele frequency (rMAF) of group A, calculated as MAF of EGFR sensitizing mutations / MAF of EGFR rare mutations, was higher than that of group B (p = 0.007). Conclusions: This study comprehensively explored the population characteristics of compound EGFR mutations from a large cohort of primary NSCLC patients, which will be helpful to guide personalized therapy and promote the clinical management of this population. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: H. Cheng: Honoraria (self): Beijing Acornmed Biotechnology Co., Ltd. H. Wang: Honoraria (self): Beijing Acornmed Biotechnology Co., Ltd. F. Lou: Honoraria (self): Beijing Acornmed Biotechnology Co., Ltd. S. Cao: Honoraria (self): Beijing Acornmed Biotechnology Co., Ltd. All other authors have declared no conflicts of interest.